Dexamethasone intake for different periods related to Blood Sugar rate in Diabetes Mellitus type 2 Patients in Thi-qar province / Iraq - Mohannad Abdulrzzak (University of Thi-Qar Journal of Science, 2019)
Dexamethasone widespread use as anti-inflammatory drugs. In Diabetes mellitus type 2 patients using of Dexamethasone has a crucial side effects including increase blood sugar rate. 106 patients involved in this study, all ofthem take Sulfonylurea tablets to control glucose level in the blood. They divided into 3 groups (depending upon periodof Dexamethasone used) group A patients intake drug for one week (30 patient), group B take the drug more than onemonth (30 patient) and third group don’t take the drug (46). Random blood sugar rate taken for all patients afterfinishing drug prescription. Results of three groups statically analysis. The mean of three groups were 242.8, 317 and217 for A,B and C respectively. There were a significant differences in level (P<0.5%) between the two groups (A,B)and control group also between group A and B .Females were prodomenet suffer from diabetes they reached 78.6%while males were 21.4%. This the study showed that patients were un educated or negligible with Dexamethasone sideeffects and took the drug without prescription.